User Acceptance Testing to Assess User Receptiveness Toward a Soft Skills Training Information System - Hermansah, Lutfi; Murhadi, Murhadi; Saputro, Wahju Tjahjo (Sistemasi: Jurnal Sistem Informasi, 2025)
Soft skills organizations face significant challenges due to manual management practices, leading to scattered participant data, lack of proper documentation, and manual archiving. The main issue is the absence of a dedicated soft skills training information system. This study aims to develop and evaluate a soft skills training information system to address these organizational problems. The Rapid Application Development (RAD) method was chosen for its ability to accommodate changing requirements and enable rapid deployment of the system. System acceptance testing was conducted using the User Acceptance Test (UAT) method with 70 respondents, covering 20 questionnaire items related to system functionality, user interface experience, performance, efficiency, and productivity. The UAT results indicated that the system received an average acceptance rate of 80.4% for functionality, 76.8% for user experience and interface design, 77.3% for performance, and 78.7% for efficiency and productivity. These results show that the soft skills training information system meets user requirements with an overall interpretation score of "Good." The developed system is considered acceptable and capable of supporting soft skills training activities at Universitas Muhammadiyah Purworejo.